Polymer Electrolyte Membrane Fuel Cell Performance of a Sulfonated Poly(Arylene Ether Benzimidazole) Copolymer Membrane. (1st December 2016) - Gerçel, Hasan Ferdi; Tosun, Çağla Gül; Akyalçın, Levent
Abstract : Disodium-3, 3′-disulfonate-4, 4′-dichlorodiphenylsulfone (SDCDPS) and 5, 5′-bis[2-(4-hydroxyphenyl)benzimidazole] (HPBI) monomers were synthesized. Binding these monomers via nucleophilic aromatic polycondensation reaction, a sulfonated poly(arylene ether benzimidazole) copolymer was synthesized. Structures of monomers and copolymer were confirmed by proton nuclear magnetic resonance spectroscopy ( 1 H NMR) and Fourier transform infrared (FTIR) spectroscopy analyses. Proton exchange membrane was prepared by dissolving copolymer in dimethylacetamide (DMAc) and casting onto a glass plate. Copolymer membrane was doped with sulfuric acid to ensure proton exchange character. Single cell performance of the copolymer membrane was tested in a polymer electrolyte membrane fuel cell test station. The highest power density of the membrane was measured as 23.7 mW cm −2 at 80°C. Thermogravimetric analysis (TGA) showed that as the degree of disulfonation is increased thermal stability of the copolymer is increased.